Uji Aktivitas Ekstrak Etanol Herba Sambiloto (Andrographis paniculata Nees) dan Biji Jinten Hitam (Nigella sativa L.) terhadap Reaksi Anafilaksis Kutan Aktif pada Tikus Putih Wistar Jantan yang Diinduksi Ovalbumin - Yeli Trimayanti; Gunawan Pamudji Widodo; Yul Mariyah (Jurnal Farmasi Indonesia, 2015)
Development of medical plants for the allergic reaction is continuing with the extrac of the bitter (Andrographis paniculata Nees) and black seed (Nigella sativa L.) as an example. This reseach’s purpose is studying inhibition of anaphylaxis reactions effect from ethanol extracts of the bitter herbs and black seed for active anaphylaxis reaction inducted by ovalbumin in male Wistar rats. Research used active anaphylaxis reaction method with 5 test groups, i.e. negative control group, positive control group and 3 tread group. The rats were subcutaneously sensitized by ovalbumin two act time with an interval of seven days. Back rats shavered and intravenaosly injected with evans blue in rats tail. Diameter area of pigmentation measured every hour, up to 8 hours. Obtained data then tested statistically using ANOVA. Results showed that the extract of bitter herbs (120 mg/kg BB), black seed (30 mg/kg BB) and combination of both (60 mg/kg BB : 15 mg/kg BB) could inhibit pigmentation in the back rats skin area. Percent inhibition respectively is 12.39 %; 14.51 %; 22.36 %. Nevertheless, the inhibitory effect was still lower compared with cromolyn sodium as an mast cell stabilizer drug. It can be concluded that the combination of bitter herbs ethanol extracts with black seed ethanol extracts more effectively inhibit active cutaneous anaphylaxis reaction of ovalbumin induced in male Wistar rats.